Measuring readiness to implement systems that create, mobilise and diffuse knowledge - Tanudjojo, J. Satrijo (Cranfield University, 2006)
This thesis focuses on pre-conditions for organisations to implement knowledge management systems (KMS). Prior research suggests knowledge management (KM) is a capability and, as such, organisations need to know if they are ready to embark on KM initiatives that develop this capability. The findings of my research contend that measuring readiness is a prerequisite for implementing KMS holistically. I argue that effective KMS integrates the creation, mobilisation and diffusion stages of the knowledge life-cycle. Therefore, a system for gauging organisational readiness for KMS necessitates understanding the organisation’s inclination to create, mobilise and diffuse knowledge. Drawing from Socio-Technical Systems (STS) Theory, this study uses three dimensions, Infrastructure, Knowledge Structure and Knowledge Culture, to gauge each stage of the knowledge life-cycle. This study develops an instrument – the Knowledge Implementation Assessment Tool (KIAT) – to assess an organisation’s readiness for KMS. An organisation’s readiness can be said to increase as the measure on each dimension increases. In addition, this study found that structurally diverse Communities For Performance are needed to leverage Communities Of Practice in delivering direct business results, and that the implementation of KMS must be governed within and by cross-functional business processes. The knowledge-based theory of the firm and the knowledge life-cycle theory provide a conceptual understanding that managing the creation, mobilisation and diffusion of knowledge can yield competitive advantage. Based on these theories, an in-depth case study was conducted in Schlumberger’s technical service delivery process. The study analysed the implementation and the use of InTouch, Schlumberger’s KMS. The case study was conducted using an Abductive research strategy. The Means-End Chain approach and its laddering technique were used to collect and analyse data to establish 35 attributes vital for the implementation of an effective KMS – one that brings beneficial results. These attributes form the basis for creating the readiness assessment instrument – KIAT. A KMS implementation affects the social and technical aspects of an organisation. This study categorised the attributes along the three STS dimensions. The basis of the categorisation was the fit between each attribute and an STS dimension. The result is an assessment instrument to measure organisational readiness. The instrument, KIAT, consists of 50 factors to measure organisational readiness along the three STS dimensions for the creation, mobilisation and diffusion of knowledge. KIAT is operationalised in three organisational cases in different industries and processes. This allowed the instrument to be refined and led to the development of procedures to apply KIAT. The cases suggest that KIAT provides useful insights to discover or confirm KMS readiness where a cross-functional business process is the unit of analysis. The research contributes to research methodology in the KM field, as it is the first to use the Means-End Chain approach into knowledge management research by representing a hierarchy of organisational goals in a knowledge management initiative. For practitioners, my research makes two contributions. One, the KIAT readiness assessment instrument to diagnose their organisational readiness and take informed decisions. Two, the understanding of Communities For Performance. This study points the way for further research. This includes directions to explore the relationship between the levels of readiness and the effectiveness of KMS implementation, the relationship between organisations’ experience and their readiness, and the relationship between the dynamics of the KIAT Factors and organisational learning.
Keywords: Knowledge Management; Knowledge Management System; Knowledge Sharing; Means-End Chain; Laddering Technique; Socio-Technical System; Organisational Development